Actions performed by the companion during the immediate care of the newborn in public maternity hospitals - Mayara Carminatti Sabino; Roberta Costa; Manuela Beatriz Velho; Odaléa Maria Brüggemann; Carolina Frescura Junges; Iris Elizabete Messa Gomes (Universidade Federal de Santa Maria, 2021)
Objective: to describe the actions performed by the woman's companion during immediate care of the newborn. Method: a descriptive quantitative study carried out in three public maternity hospitals in Greater Florianópolis, Santa Catarina, Brazil, with 1,075 respondents between March 2015 and May 2016; and descriptive statistical analysis was applied. Results: in the actions carried out, the following stood out: talking to the newborn (94.8%); petting (93.0%); calming down (78.3%); picking up (81.4%); assisting in first feeding (67.6%); and leading him to the mother (58.4%). The following were less frequent: giving the first bath (7.9%); cutting the umbilical cord (20.4%); and putting the diaper on (26.7%). Conclusion: the companion's participation in caring for the newborn shows actions of a sentimental, affective and caring nature, as well as facilitating the establishment of family bonds. Knowing the actions taken by the companion contributes to the care practice, with the possibility of expanding their participation and providing greater meaning for the woman and the family.